Software architecture and algorithm for reliable RPC for geo-distributed mobile computing systems - Khan, Asmat Ullah; Bagchi, Susmit (Future generation computer systems, 2018)
Remote Procedure Call (RPC) is a computing as well as communication model for distributed processes to execute client routines on remote servers in the distributed systems. Due to the evolution of geo-distributed mobile cloud computing systems, mobile devices are exposed to frequent disconnection due to limited battery lifetime, processing capacity and network bandwidth while roaming globally. The existing standard RPC and mobile RPC frameworks are not completely suitable for applications in geo-distributed mobile cloud computing. This paper proposes a novel software architecture and associated algorithms for realizing reliable RPC under global mobility of clients. The stateful server chaining and multiple authentication primitives are employed in the proposed design to achieve security as well as location transparency. The software architecture is implemented on heterogeneous testbed and evaluated with promising results. The heterogeneity of mobile cloud platform is considered in the design by employing specific XDR format enhancing portability. A detailed comparative analysis of the proposed design is included in the paper. •GMCC-RPC: Reliable mobile RPC for geo-distributed systems.•Software architecture for mobile and reliable RPC for geo-distributed systems.•Mobile and Reliable RPC using server chains in geo-distributed systems.